What was Killing Babies in Amsterdam? A Study of Infant Mortality Patterns Using Individual-Level Cause of Death Data, 1856–1904 - Janssens, Angélique; Riswick, Tim (Historical Life Course Studies, 2023)
Based on unique individual-level cause of death data, this article presents an analysis of the development of infant mortality and the underlying cause of death pattern in the city of Amsterdam in the period 1856–1904. We contribute to the discussion on the development of infant mortality and its determinants and test the newly-constructed ICD10h coding system. First, our results demonstrate that the ICD10h and groupings of causes worked quite well for our period and city data. Second, Amsterdam moved from being one of the most lethal cities in the country to one of the healthiest for infants. These improvements in the fate of infants were brought about despite faltering progress in the provision of piped water, and an absence of modern sewerage throughout the period. For the entire period air-borne diseases were a prominent cause of death category, peaking in the 1880s and still making up the major group of diseases by 1904. Water- and food related ailments were also dominating the epidemiological pattern after the 1870s. Vague or ill-defined disease terms were frequent at the start of the study period. These observations suggest that physicians were increasingly better able and more prepared to formulate more precise disease terms by the 1900s. The seasonality analysis of the different disease groups demonstrates strong summer effects on the group of water- and food related causes of death. It testifies to the shortcomings in the city’s hygienic situation and limited breastfeeding.